2019
DOI: 10.1177/0306624x19870374
|View full text |Cite
|
Sign up to set email alerts
|

A Principled Approach to the Construction of Risk Assessment Categories: The Council of State Governments Justice Center Five-Level System

Abstract: Consistent risk category placement of criminal justice clients across instruments will improve the communication of risk. Efforts coordinated by the Council of State Governments (CSG) Justice Center led to the development of a principled (i.e., a system based on a given set of procedures) method of developing risk assessment levels. An established risk assessment instrument (Level of Service Inventory–Revised [LSI-R]) was used to assess the risk-level concordance of the CSG Justice Center Five-Level s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…Conceptually, the process of calculating the 5-Level System's levels is not complicated (see Kroner et al, 2020, for a demonstration). In practice, however, aligning tools to the framework is not straightforward; Hogan (2020) wrote extensively about the early practical challenges encountered by researchers.…”
Section: Features Of the Five-level Risk And Needs Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptually, the process of calculating the 5-Level System's levels is not complicated (see Kroner et al, 2020, for a demonstration). In practice, however, aligning tools to the framework is not straightforward; Hogan (2020) wrote extensively about the early practical challenges encountered by researchers.…”
Section: Features Of the Five-level Risk And Needs Systemmentioning
confidence: 99%
“…In practice, however, aligning tools to the framework is not straightforward; Hogan (2020) wrote extensively about the early practical challenges encountered by researchers. Specifically, Hogan (2020) critiqued the existing research on the 5-Level System for its focus on specific subtypes of recidivism (violent and sexual recidivism) rather than general recidivism (e.g., Davies et al, 2020;Hanson, Babchishin, et al, 2017;Hogan & Sribney, 2019;Olver et al, 2018Olver et al, , 2021 change in prediction timeframe to 5-year outcomes (e.g., all except Kroner et al, 2020), and researchers' decision to split Level IV into sublevels (Level IVa and IVb) because expected recidivism rates did not reach the lowest bound of Level V (85%; even using general recidivism outcomes, for example, Kroner et al, 2020). Such adaptations to the guidelines show that to build agreement about standardization, the field will require an encompassing and collective program of research to avoid so many individualized deviations that forensic practitioners would potentially need to offer qualifications about each tool, jurisdiction, and assessment situation.…”
Section: Features Of the Five-level Risk And Needs Systemmentioning
confidence: 99%
“…Nevertheless, Coulter et al (2019) did identify 4.1% of a New Zealand community sample (N = 440) as Level V for the Roc*RoI (Bakker et al, 1999) based on expected recidivism rates of over 85% within two years. In contrast, Kroner et al (2020) did not identify any individuals as Level V in two large, US community samples (N = 24,936 and N = 36,303). The lack of a Level V may also be attributed to the current sample being exclusively individuals with a sexual offending history, who tend to have lower general (overall) recidivism rates than individuals convicted of other crimes (Stewart et al, 2019).…”
Section: Resultsmentioning
confidence: 62%
“…The New Zealand community corrections study found that most individuals fell into Level III (21%) and IV (54.5%) when using their tool, the Roc*RoI (Coulter et al, 2019). The two US community samples also found most individuals fell into Level III (40% in Sample 1, 19% in Sample 2) and Level IV (32% in Sample 1, 71% in Sample 2; Kroner et al, 2020). This is not surprising, as men with sexual offences typically score lower on general criminality than men with nonsexual offences (e.g., Craig et al, 2006).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation